The Topical Effect of rhGDF-5 Embedded in a Collagen–Gelatin Scaffold for Accelerated Wound Healing - Eisler, Wiebke; Held, Manuel; Rahmanian-Schwarz, Afshin; Schiefer, Jennifer; Rahmanian, Shahab; Daigeler, Adrien; Baur, Jan-Ole (Applied Sciences, 2022)
The application of exogenous growth factors such as the recombinant human growth and differentiation factor 5 (rhGDF-5) represents a major research topic with great potential for the treatment of complex wounds. In a randomized, controlled minipig study, the topical effect of rhGDF-5 on full-thickness skin defects was evaluated. A total of 60 deep dermal wounds were either treated with rhGDF-5 embedded in an innovative collagen scaffold or another commonly used collagen matrix or left untreated. Wound healing was analyzed by planimetric analysis to determine wound closure over time. After 21 days, the areas of the initial wounds were excised, and the newly formed tissue was examined histologically. In comparison to untreated wounds, all examined matrices accelerated dermal wound healing. The largest acceleration of wound healing was seen with the high-dose rhGDF-5-treated wounds, which, compared to the untreated wounds, accelerated wound healing by 2.58 days, improved the neoepidermal thickness by 32.40 µm, and increased the epidermal cell density by 44.88 cells. The innovative collagen scaffold delivered rhGDF-5 adequately, served as a template to guide proliferating and restructuring cells, and accelerated wound healing. Thus, this composite product offers a novel tool for developing effective wound dressings in regenerative medicine.
CRIS-Team Scopus Importer:2022-01-28
Keywords: Collagen scaffold; Composite biomaterial; Growth factor; RhGDF-5; Wound healing